Two kinds of simple-minded ethics: the practical a recentiori and the existential a satori - Bańka, Józef (Folia Philosophica, 2010)
The aim of the paper is to discuss two kinds of simple-minded ethics taken as intention of justified understanding of the world. This intention, which is not rooted even in science, is intuitively unfailing. Both kinds of ethics include specific keywords: a recentiori (derived from „now”) expresses the opinion according to which everything we recognize is recognized for the first time, whereas a satori (Sanskrit - „from awakening”) refers to mystical transformation of personality. The comparison between them is made on the ground provided by recentivism according to which description of certain phenomenon may be taken as justified in a real-time only. In both cases the migrating element (recens), which is aimed at self-perfection and nirvana, stands out. At the same time it is a common element for both kind of ethics.